The Effectiveness of a Supervision Program in Developing the Counselling Supervision Skills of Student Guidance Female Supervisors at the Directorate General of Education in Makkah Province - Al-Sharif, Amjad Ibrahim; Al-Malki, Hanan Abdulrahim (Journal of Educational and Psychological Sciences, 2025)
This study aimed to verify the effectiveness of a supervision program in developing the counselling supervision skills of student guidance female supervisors at the Directorate General of Education in Makkah Province. To achieve the study objectives, a- two- group- quasi-experimental approach was used, the experimental group and the control group, with (pre-post-and tracking) measurements. The study sample consisted of 20 female supervisors, randomly drawn and divided into two groups: an experimental group with 10 female supervisors, and a control group with10 female supervisors. A guidance supervision skills scale, and a supervisory program based on a differential model of supervision, all prepared by the researcher. The study revealed that there were statistically significant differences at the (α≤0.05) level between the means of the experimental group members’ scores in the pre- and post-measurements of counseling supervision skills in favor of the post-measurement. There were statistically significant differences at the (a ≤ 0.01) level between the means of the scores of experimental and control groups in the post-measurement of counseling supervision skills in favor of the experimental group. However, there were no statistically significant differences between the means of the experimental group members’ scores in the post and tracking measurements of counseling supervision skills. The researcher recommends applying the supervision program to all female supervisors.
Keywords: supervision program; counseling supervision skills; female supervisors